The effect of endogenously-determined bullying on test scores - Yacob Patel, Hisham bin (Institutional Knowledge at Singapore Management University, 2020)
The problem of bullying is one of the main sources of adverse school environment. In this dissertation, I explore the effect of bullying on test scores, under the assumption that bullying is endogenously determined. Comparing my estimates with that from traditional OLS, I find that estimates from OLS grossly underestimates the effect of bullying on short-term student outcomes. I also find significant evidence of heterogeneity across various sub-groups; for example, male students are found to be less affected by bullying as compared to their female peers. Furthermore, male students are also found to be less affected by physical bullying while female students are found to be more affected by relational bullying. In addition, I find some evidence suggesting the possibility of an age-trend with respect to the effect of bullying, with older students being less affected than their younger peers, both within and across cohorts. Exploring possible mechanisms, I observe that bullying victims have a poorer perception of self and often negatively evaluate their teachers. Furthermore, these students are also more likely to perceive unfair treatment by their teachers, as well as report lower levels of interest in their studies.